Estilos de crianza parental y autonomía en niños de la Institución Educativa Inicial N° 529 San José, Iquitos 2024 - Manihuari Perez, Natalia Geraldine (2024)
The purpose of this research was to determine the association between parenting styles and autonomy in children at the educational institution 529 San José, Iquitos 2024. The sample consisted of 222 children. The research follows a quantitative approach, basic level, non-experimental, and relational design. The results indicated a significant association between the study variables, with a p-value < 0.01 < α = 0.05, and the strength of this association was determined using Kendall's Tau-B statistic (τ = 0.561), indicating a moderate level. These results suggest that the parenting styles practiced by the parents are connected to the children's performance in autonomy. It was concluded that there is a positive and significant relationship between the variables of parenting styles and the autonomy of the study participants.